Stromal Features of the Primary Tumor Are Not Prognostic in Genetically Engineered Mice of Pancreatic Cancer - Marie C. Hasselluhn; Lukas Klein; Melanie S. Patzak; Sören M. Buchholz; Philipp Ströbel; Volker Ellenrieder; Patrick Maisonneuve; Albrecht Neesse (Cells, 2019)
The KrasG12D/+;LSL-Trp53R172H/+;Pdx-1-Cre (KPC) mouse model is frequently employed for preclinical therapeutic testing, in particular in regard to antistromal therapies. Here, we investigate the prognostic implications of histopathological features that may guide preclinical trial design. Pancreatic tumor tissue from n = 46 KPC mice was quantitatively analyzed using immunohistochemistry and co-immunofluorescence for proliferation (Ki67), mitotic rate (phospho-Histone 3, PHH3), apoptosis (cleaved caspase-3, CC3), collagen content, secreted protein acidic and rich in cysteine (SPARC), hyaluronic acid (HA), and α-smooth muscle actin (α-SMA). Furthermore, mean vessel density (MVD), mean lumen area (MLA), grading, activated stroma index (ASI), and fibroblast-proliferation rate (α-SMA/Ki67) were assessed. Univariate analysis using the Kaplan−Meier estimator and Cox regression model for continuous variables did not show association between survival and any of the analyzed parameters. Spearman correlation demonstrated that desmoplasia was inversely correlated with differentiated tumor grade (ρ = −0.84). Ki67 and PHH3 synergized as proliferation markers (ρ = 0.54), while SPARC expression was positively correlated with HA content (ρ = 0.37). MVD and MLA were correlated with each other (ρ = 0.31), while MLA positively correlated with CC3 (ρ = 0.45). Additionally, increased MVD was correlated with increased fibroblast proliferation rate (α-SMA + Ki67; ρ = 0.36). Our pilot study provides evidence that individual histopathological parameters of the primary tumor of KPC mice are not associated with survival, and may hint at the importance of systemic tumor-related effects such as cachexia.